CDX2-Suppressed Colorectal Cancers Possess Potentially Targetable Alterations in Receptor Tyrosine Kinases and Other Colorectal-Cancer-Associated Pathways - Ioannis A. Voutsadakis (Diseases)
Background: Colorectal cancer, a prevalent gastrointestinal carcinoma, has a high risk for recurrence when locally advanced and remains lethal when in an advanced stage. Prognostic biomarkers may help in better delineating the aggressiveness of this disease in individual patients and help to tailor appropriate therapies. CDX2, a transcription factor of gastrointestinal differentiation, has been proposed as a biomarker for good outcomes and could also be a marker of specific sub-types amenable to targeted therapies. Methods: Colorectal cancers from The Cancer Genome Atlas (TCGA) colorectal cohort and colon cancers from the Sidra-LUMC AC-ICAM cohort were categorized according to their expressions of CDX2 mRNA. Groups with CDX2 suppression were compared with cancers showing no suppression regarding their clinical and genomic characteristics. Results: CDX2-suppressed colorectal cancers showed a high prevalence of Microsatellite Instability (MSI) and a lower prevalence of chromosomal Instability (CIN) compared to non-CDX2-suppressed cancers. In addition, CDX2-suppressed cancers had a higher prevalence of mutations in several receptor tyrosine kinase genes, including EGFR, ERBB3, ERBB4, RET, and ROS1. In contrast, CDX2-suppressed cancers displayed lower mutation frequencies than non-CDX2-suppressed cancers in the genes encoding for the two most frequently mutated tumor suppressors, APC and TP53, and the most frequently mutated colorectal cancer oncogene, KRAS. However, CDX2-suppressed colorectal cancers had a higher prevalence of mutations in alternative genes of the WNT/APC/β-catenin and KRAS/BRAF/MEK pathways. In addition, they showed frequent mutations in DNA damage response (DDR) genes, such as BRCA2 and ATM. Conclusion: CDX2-suppressed colorectal cancers constitute a genomically distinct subset of colon and rectal cancers that have a lower prevalence of KRAS, APC, and TP53 mutations, but a high prevalence of mutations in less commonly mutated colorectal cancer genes. These alterations could serve as targets for personalized therapeutics in this subset.